Blastic Plasmacytoid Dendritic Cell Neoplasm Evaluated by FDG PET/CT. (July 2017) - Li, Zu-Gui; Mu, Hai-Yu
Abstract : Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematological malignancy. A 34-year-old man with a biopsy-proven BPDCN underwent FDG PET/CT for staging. FDG PET/CT revealed multiple mild FDG-avid cutaneous lesions on the chest and back, involvement of left inguinal lymph node, and a markedly increased FDG-avid subcutaneous mass in the left lower leg.